Issues of Immigration in Jordan between Local and Arab Regional Legislations - Qerbaa, Mohammad; Mashaqbeh, Amin (Dirasat: Human and Social Sciences, 2019)
This study aimed to address an important issue related to the absence of Jordanian legislative formulas governing asylum and refugee cases because there is a real reason that compels Jordan to formulate such laws regarding asylum and refugees because it has become a home of expertise at the regional and international levels due to the repetition of these events. This study was designed to deal with the misdiagnosed interpretations of the legal error in the absence of a Jordanian legal article interpreting the legal legislation of asylum.Therefore, this study dealt with the reasons behind the lack of Jordanian legislation on asylum issues, and reached a number of results related to the overall internal and external circumstances, including economic and political, and these conditions hindered the creation of legal formulations.The study concluded with recommendations that take into account all the specificities so as not to cause any sensitivity between Jordan and other countries.